Improving conditions of service for family caregivers in South Africa - Pule, Tebogo; Costa, King (My University, 2020)
Introduction: In most cases chronically-ill patients, the disabled and old persons are discharged from healthcare facilities to their families who have inadequate knowledge and skill. They may not be familiar with the kind of care expected to provide. The healthcare system does not provide continuity of care, especially to the family caregiver. The family caregiver is left to attend to the physical, economical, psychological needs of the patient with limited to no support from the healthcare system. This poses a huge challenge and increases the burden for the family caregiver which ends up becoming unbearable to the point where the process is no longer a healthy or viable option for both the caregiver and care recipient. The role of the caregiver in a patient’s health is often overlooked or underestimated in the South African health system, as a result, the caregiver is not recognized as part of the health system policy and financial inclusions. The aim of this study is to conduct a Qualitative Systematic Review of the conditions of service for family caregivers across four dimensions namely: Problems/challenges, burden, intervention and outcome, in South Africa. Method: A Qualitative Systematic Review was conducted, following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) methodology on Google Scholar database, and retrieved articles from 1994 to 2020. Following Boolean operators, words “AND”, “OR” and “NOT”, were used, to search key terms “family caregiving in South Africa”, “primary caregiving” or “informal caregiving”. Rigor was determined and documented throughout in order to allow readers to access its completeness. Inclusion and exclusion criteria were clearly outlined. Criteria for evaluating primary studies were clearly defined at the beginning of undertaking research. A total of 1810 articles, reports and dissertations were retrieved and only 85 studies were included in the review. Findings and Discussion: Studies were critically appraised using WebQDA software, whereby 198 comments emerged. Both the burden and challenges of caregiving experienced were categorized as problems, which came out 82 times (68%) compounding the role that they play. Other categories that emerged from the studies were Intervention and outcome which came out 53 and 13 times respectively. Interventions and outcome were also consolidated into one group, implying that interventions would have an impact on improving or declining outcome and these were only 32%. Four final themes emerged out of this research.
Keywords: conditions of service; family caregiving